Unveiling the mission statements in social enterprises: a comparative content analysis of US- vs. Spanish-based organizations. Issue 2 (4th May 2017) - Mas-Machuca, Marta; Ballesteros-Sola, Maria; Guerrero, Adrián
ABSTRACT: Mission statements are widely considered an effective strategic and communication tool in all types of organization. Specifically, mission statements are also relevant in social enterprises. Our study examines and describes the mission statements in a sample of 117 Spanish social enterprises and compares them with previous research on US-based social enterprises' mission statements. A manual content analysis of those mission statements was independently performed by three researchers. A two-sample t -test was performed to test the difference between these two independent US-based and Spanish samples. Our findings suggest that the degree of development of Spanish social enterprises' mission statements is still in an embryonic state. Additionally, results show that there are significant differences between the components of the social enterprises' mission statements in Spain and the USA. Mission statements in Spain tend to emphasize customers, products, services and the company philosophy. This study has implications for practitioners, as it highlights the need to elevate the quality of Spanish social enterprises' mission statements, as well as for researchers, as we uncover future research opportunities that are context specific.